Nitrogen fertilization in off-season corn crop in different Brazilian Cerrado environments - Simão, Eduardo de Paula; Resende, Álvaro Vilela de; Gontijo Neto, Miguel Marques; Silva, Alexandre Ferreira da; Godinho, Vicente de Paulo Campos; Galvão, José Carlos Cardoso; Borghi, Emerson; Oliveira, Antônio Carlos de; Giehl, Jeferson (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to assess the grain yield and the economic response of off-season corn (Zea mays) crop subjected to different combinations of starter and topdressing nitrogen fertilization, in the Brazilian Cerrado region. The experiment was carried out in a randomized complete block design in a 3×4 factorial arrangement (0, 45, and 90 kg ha-1 N at sowing and 0, 22.5, 45, and 90 kg ha-1 N in topdressing as urea), in six environments, combining three sites and two sowing times. Grain yield was determined, and the response to total N applied as starter and topdressing was used to obtain a general model of the average trend of the technical and economic return of fertilization. The corn crop response varied according to the environment, and the observed yields were high. The application of N as a starter fertilizer increased corn yield and improved the effect of topdressing fertilization or even made it unnecessary. Fertilization with 90 kg ha-1 N as urea promotes greater yield and economic return and improves N balance in the soybean/off-season corn crop system.
Keywords: Zea mays; efficient N use; N requirement; second corn crop; soybean-corn succession